Herpes Zoster Burden in Canadian Provinces: A Narrative Review and Comparison with Quebec Provincial Data - Marie-Claude Letellier; Rachid Amini; Vladimir Gilca; Gisele Trudeau; Chantal Sauvageau (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. The main aim of this review was to assess incidence rates and trends of medically attended and death cases of herpes zoster in Canada. Methods. The search was conducted in five databases (PubMed, Cochrane, Embase, PsycNET, and Web of Science). Data on herpes zoster-related consultations and hospitalisations and deaths were also extracted from three Quebec provincial administrative databases (RAMQ, MED-ECHO, and ISQ). Results. The electronic search yielded 587 publications. Seventeen publications satisfied inclusion criteria. These publications reported data from eleven studies. Ten studies used provincial databases, and one study used the Canadian Primary Care Sentinel Surveillance Network electronic database. Seven studies evaluated overall rates of medically attended cases (consultations and hospitalisations). Four of these studies reported an increase in rates of medically attended cases during the study period; one study reported stable rates, and two studies reported only an average rate. The rates varied from 316 to 450/100,000 p.y. The Quebec analysis shows similar rates with a slight decreasing trend (from 369 to 350/100,000 p.y.). Incidence rates of consultations were reported separately in three studies. Two studies reported an increase in rates (from 258 to 348/100,000 p.y. and from 324 to 366/100,000 p.y.), and the third study reported a decrease (from 525 to 479/100,000 p.y.). Hospitalization rates were reported separately in two studies, both reporting a decrease (from 12 to 8 cases/100,000 p.y. and from 9 to 4 cases/100,000 p.y.). Quebec data also showed a decrease, from 9 to 6 cases/100,000 p.y. One study reported herpes zoster-related deaths. In this study, the reported death rate was 0.7/1,000,000 p.y. in the overall population and 5.5/1,000,000 p.y. in those aged ≥65 years. Quebec analysis showed a death rate of 1.2/1,000,000 p.y. in the overall population and 8.6/1,000,000 p.y. in those aged ≥65 years. Conclusions. The results of the reviewed studies and our analysis of Quebec provincial data indicate important variations in the reported overall incidence rates of medically attended herpes zoster cases in Canada. The trends in time are heterogeneous in studies in which hospitalisations and medical consultations were pooled together. We observed a decrease in hospitalization rates and a slight increase in consultation rates in studies reporting hospitalisations and consultations separately. These results consolidate the understanding of the herpes zoster burden in Canada and might be used as a tool in decision-making regarding future preventive interventions.